Pengaruh Likuiditas, Kualitas Aset, Sensitivitas, Efisiensi Dan Profitabilitas Terhadap Permodalan Pada Bank Pemerintah - Amelia Nur Ayuni; Anggraeni Anggraeni (MediaTrend, 2022)
Capital Adequacy Ratio (CAR) is one of the indicator that used to measure thebank’s capital. The aims of this study are to investigate the effecs simultaneouslyand partially from Loan to Deposit Ratio (LDR), Investing Policy Ratio (IPR),Adverserly Classified Asset (APB), Non Performing Loan (NPL), Interest Rate Risk(IRR), Net Open Position (PDN), Operational Efficiency Ratio (BOPO), Fee BasedIncome Ratio (FBIR), Return On Asset (ROA) on CAR and which variable has thedominant effect on CAR. This study used secondary data taken from first periodquarterly of 2014 until the fourth quarterly of 2019 of government banks. This studyused sensus that consists PT Bank Mandiri Tbk, PT Bank Negara Indonesia Tbk,PT Bank Rakyat Indonesia Tbk, and PT Bank Tabungan Negara Tbk. The datawere processed by using SPSS 21. The result of this study revealed that LDR, IPR,APB, NPL, IRR, PDN, BOPO, FBIR, and ROA simultaneously have significanteffect on CAR. PDN and FBIR partially have significant effects on CAR. PDN isthe dominant variable that influences CAR.